2D sp2 Carbon‐Conjugated Porphyrin Covalent Organic Framework for Cooperative Photocatalysis with TEMPO. Issue 23 (26th March 2020) - Shi, Ji‐Long; Chen, Rufan; Hao, Huimin; Wang, Cheng; Lang, Xianjun
Abstract: 2D covalent organic frameworks (COFs) are receiving ongoing attention in semiconductor photocatalysis. Herein, we present a photocatalytic selective chemical transformation by combining sp 2 carbon‐conjugated porphyrin‐based covalent organic framework (Por‐sp 2 c‐COF) photocatalysis with TEMPO catalysis illuminated by 623 nm red light‐emitting diodes (LEDs). Highly selective conversion of amines into imines was swiftly afforded in minutes. Specifically, the π‐conjugation of porphyrin linker leads to extensive absorption of red light; the sp 2 −C=C− double bonds linkage ensures the stability of Por‐sp 2 c‐COF under high concentrations of amine. Most importantly, we found that crystalline framework of Por‐sp 2 c‐COF is pivotal for cooperative photocatalysis with (2, 2, 6, 6‐tetramethylpiperidin‐1‐yl)oxyl (TEMPO). This work foreshadows that the outstanding hallmarks of COFs, particularly crystallinity, could be exploited to address energy and environmental challenges by cooperative photocatalysis. Abstract : Red, Go ! An effective protocol for the selective oxidation of amines into imines was unveiled by cooperative photocatalysis of Por‐sp 2 c‐COF and TEMPO illuminated by 623 nm red LEDs.